Liver Stiffness Is a Predictor of Rebleeding in Patients With Hepatitis B-Related Cirrhosis: A Real-World Cohort Study - Liu, Linxiang; Nie, Yuan; Zhang, Yue; Liu, Qi; Zhu, Xuan (Frontiers in Medicine, 2021)
Background: Esophageal vein rebleeding is a life-threatening complication of liver cirrhosis. However, the role of noninvasive methods that were developed to evaluate the severity of chronic liver disease, especially in rebleeding, remains unclear. Aims: To evaluate the performance of liver stiffness and noninvasive fibrosis scores in predicting esophageal vein rebleeding in HBV cirrhotic patients. Methods: A prospective analysis of 194 HBV patients between 2017 and 2021 was performed. Receiver operating characteristic (ROC) curves and time dependent ROC curves were used to assess the power for predicting rebleeding with noninvasive fibrosis score and liver stiffness. Results: During the median follow-up time of 68.28 weeks, 55 patients experienced rebleeding. In the entire cohort, the area under the ROC curve for liver stiffness measurement (LSM) predicting for rebleeding was 0.837, and the time-dependent ROC curve also showed stable prediction performance of LSM. The predictive ability of the noninvasive fibrosis score was less than that of LSM, and there were statistical differences. Moreover, patients using nonselective beta blockers and HBV DNA-negative patients experienced significantly reduced rebleeding. Conclusions: Compared with noninvasive fibrosis scores, LSM can more simply and accurately predict rebleeding events of hepatitis B liver cirrhosis.